2019
DOI: 10.3390/su11123319
|View full text |Cite
|
Sign up to set email alerts
|

Benefit–Cost Analysis of Green Roof Initiative Projects: The Case of Jung-gu, Seoul

Abstract: Green roofs, which have various economic, environmental and social effects, have been acknowledged as an alternative green space in urban areas. This study aims to investigate the economic feasibility of green roof projects by conducting a benefit–cost analysis on the case of Jung-gu, Seoul. The analysis estimates and compares five different scenarios applied in the study area with a 20-year operation period in all cases. This set of scenarios aims to compare the most idealistic situation with more achievable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
1
20
0
1
Order By: Relevance
“…Reduced support was due to the limitations of middle and low-income people who had minimal residential land. The results of this study indicated significant findings by Eunha Shin and Heungsoon Kim [9] that from an economic aspect, indeed, a green-roof required more cost than a conventional roof. Thus, the role of high-income community participation would be more supportive than middle-income or even low-income communities.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Reduced support was due to the limitations of middle and low-income people who had minimal residential land. The results of this study indicated significant findings by Eunha Shin and Heungsoon Kim [9] that from an economic aspect, indeed, a green-roof required more cost than a conventional roof. Thus, the role of high-income community participation would be more supportive than middle-income or even low-income communities.…”
Section: Discussionsupporting
confidence: 50%
“…The benefits of green-roof contribute to some environmental aspects, including increasing biodiversity, reducing the effects of urban heat island [1][2][3][4][5], decreasing the thermal temperature of buildings [6][7][8]; on the economic aspect, including reducing maintenance costs and lowering operational costs [9][10][11]; and on aspects of social space, where people have access to green areas [12][13][14]. Economically, green-roof initiatives are feasible under certain conditions, but consideration needs to be paid to the construction costs of green-roof for the entire roofs of the buildings [9]. Another benefit, added by Muhammad , is through research on green-roof related to hydrology in Seoul.…”
Section: Prospect Of Green Roofs Toward Sustainability Developmentmentioning
confidence: 99%
“…The promotion of urban GRs has always been a discussion topic in academia. The mainstream literature focuses on GR technology, benefits, design and so on [29,30]. In comparison, studies on GR policies were less numerous.…”
Section: Introductionmentioning
confidence: 99%
“…A benefit–cost analysis in Jung‐gu, Seoul, South Korea, compared five potential green roof projects, primarily focused on percent coverage of roofs. The study identified costs (structural safety inspection, construction, operation and maintenance, safety management and environment, and disposal) and benefits (carbon sequestration, reduction in cooling energy, stormwater management, air pollutant removal, social benefits of improved air quality, rooftop lifetime extension, urban aesthetics, and comfort) of green roof projects (Shin & Kim, 2019). The only scenario which produced a greater benefit than cost was implementation of green roofs on all rooftops.…”
Section: Green Roofsmentioning
confidence: 99%